Niger Service Delivery Indicators : Health 2015 - World Bank (Washington, DC, 2017)
The Service Delivery Indicators (SDI) program aims to document what results are obtained through public spending in the health and education sector. The focus is on the individual dimensions, whether effort (presence and workload) or knowledge (diagnostic accuracy, adherence to clinical guidelines, and case management). These dimensions are not routinely measured and reported publicly in a comparable fashion, yet are among the factors that influence policy outcomes in health. The remainder of this document is organized into three major sections: methodology and implementation; results; and implications for Niger. Annexes present details of the sampling strategy, definitions of the indicators, and additional results. A final section presents the references consulted or cited.